2019
DOI: 10.1371/journal.pone.0215277
|View full text |Cite
|
Sign up to set email alerts
|

Necrosis, apoptosis, necroptosis, three modes of action of dopaminergic neuron neurotoxins

Abstract: Most of the Parkinson’s disease (PD) cases are sporadic, although several genes are directly related to PD. Several pathways are central in PD pathogenesis: protein aggregation linked to proteasomal impairments, mitochondrial dysfunctions and impairment in dopamine (DA) release. Here we studied the close crossing of mitochondrial dysfunction and aggregation of α-synuclein (α-syn) and in the extension in the dopaminergic neuronal death. Here, using rat primary cultures of mesencephalic neurons, we induced the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 39 publications
3
54
0
1
Order By: Relevance
“…The addition of 25 μM 6-0HDA for 24 h led to a decrease in cell viability of 50%, as shown in Figure 2 B. The dose and incubation time for this neurotoxin is variable, according to the scientific data available, varying from 5 to 100 μM and from 30 min to 48 h [ 57 , 58 , 59 , 60 ]. That is why we incubated the neuronal cells with different doses for 24 h, an intermediate time point in the published articles, and selected the dose that generated 50% cell death so we could really see the effect of the neurotoxin on cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of 25 μM 6-0HDA for 24 h led to a decrease in cell viability of 50%, as shown in Figure 2 B. The dose and incubation time for this neurotoxin is variable, according to the scientific data available, varying from 5 to 100 μM and from 30 min to 48 h [ 57 , 58 , 59 , 60 ]. That is why we incubated the neuronal cells with different doses for 24 h, an intermediate time point in the published articles, and selected the dose that generated 50% cell death so we could really see the effect of the neurotoxin on cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…In these models, neuronal cell death associated with mutations in PD‐linked genes ( SNCA, LRRK2 , DJ‐1, PARK2 , PINK‐1) involves varying degrees of activation of intrinsic (Iaccarino et al, ; Yamada, Iwatsubo, Mizuno, & Mochizuki, ) and extrinsic (Ho, Rideout, Ribe, Troy, & Dauer, ) apoptosis, autophagic cell death (Venderova & Park, ), and parthanatos (Kam et al, ). Similarly, intrinsic (Clayton, Clark, & Sharpe, ; Perier et al, ) and extrinsic (Hayley et al, ) apoptosis, necroptosis (Callizot, Combes, Henriques, & Poindron, ), and parthanatos (David, Andrabi, Dawson, & Dawson, ) are implicated in dopamine neuron death resulting from the administration of PD‐mimetic toxins MPTP, rotenone, and 6‐OHDA, albeit to differing extents.…”
Section: Ros Accumulation and Cell Death Pathwaysmentioning
confidence: 99%
“…Other data suggest that, independent of the cell death pathway targeted, cells at risk may eventually die by alternative mechanisms (Hartmann et al, ) driven by primary pathogenic factors upstream, including oxidative stress. Multiple cell death pathways may also be activated within a given neuron (Callizot et al, ), and degeneration within different neuronal compartments (axon, soma) may be governed by different pathways (Ries et al, ). Further, blockade of penultimate cell death pathway components (caspases, Apaf‐1) may prevent neuron death but not preserve or improve cellular functions disrupted by primary pathogenic factors (Levy et al, ).…”
Section: Ros Accumulation and Cell Death Pathwaysmentioning
confidence: 99%
“…Hong et al [30] found that rotenone induced necrotic cell death in PC12 cells. Recently, Callizot et al [6] have shown that rotenone treatment resulted in necrotic cell death of primary rat dopaminergic neurons at higher concentrations. According to Skulachev [69], rotenone seems to induce necrotic cell death through ATP depletion.…”
Section: Necrotic Cell Deathmentioning
confidence: 99%
“…In addition to apoptotic and necrotic cell death, rotenone was reported to lead to necroptosis in primary rat dopaminergic neurons as measured by the upregulation of RIPK3 after 24 h of exposure [6]. Upregulation of RIPK3 is an indicator of necroptotic cell death [47].…”
Section: Necroptotic Cell Deathmentioning
confidence: 99%